2014 IEEE/RSJ International Conference on Intelligent Robots and Systems 2014
DOI: 10.1109/iros.2014.6942731
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Reinforcement Learning algorithms and features for robot navigation in crowds: An experimental comparison

Abstract: International audience— For mobile robots which operate in human pop-ulated environments, modeling social interactions is key to understand and reproduce people's behavior. A promising approach to this end is Inverse Reinforcement Learning (IRL) as it allows to model the factors that motivate people's actions instead of the actions themselves. A crucial design choice in IRL is the selection of features that encode the agent's context. In related work, features are typically chosen ad hoc without systematic eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(92 citation statements)
references
References 13 publications
0
92
0
Order By: Relevance
“…As mentioned in Sect. 2, Vasquez et al [82] investigated different cost features. They concluded that social forces showed the best results for the learned scenes while being at the same time the ones generalizing worst for unknown scenes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in Sect. 2, Vasquez et al [82] investigated different cost features. They concluded that social forces showed the best results for the learned scenes while being at the same time the ones generalizing worst for unknown scenes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kim and Pineau [36] proposed to use the population density and velocity of the surrounding objects. The effect of the different features in [29] and [36] were investigate by Vasquez et al [82] and compared with social force features [28]. Results showed that the social force features perform best when applied specifically for the learned scene, but seem to generalize worst to other scenes.…”
Section: Related Workmentioning
confidence: 99%
“…Related to ViBe are several existing LfD methods that learn road and pedestrian behaviour [29], [30], [31], [32]. Most relevant is learning highway merging behaviour [33], [34] from NGSIM [35], a publicly available dataset of vehicle trajectories.…”
Section: B Learning From Demonstrationmentioning
confidence: 99%
“…This is more robust than policy search, because rewards are better generalizable and more succinct (see Vasquez et al, 2014). We use Bayesian IRL (Michini and How, 2012) to learn a distribution over the rewards and select the best reward as the MAP estimate.…”
Section: Behavior Learning Via Inverse Reinforcement Learningmentioning
confidence: 99%